Clinical and structural damage outcomes in axial spondyloarthritis patients receiving NSAIDs or advanced therapies: a description of a real-life cohort - Mocritcaia, Anastasia; Chacur, Chafik; Adao Abe, C. D.; Azuaga-Piñango, Ana Belén; Frade-Sosa, Beatriz; Sarmiento-Monroy, Juan C.; Alascio, Lucia; Gómez-Puerta, J. A.; Sanmartí, Raimon; Cañete, Juan D.; Ramírez, Julio (Frontiers in Medicine, 2024)
This study aims to describe the clinical characteristics, disease activity, and structural damage in patients with axial spondyloarthritis (axSpA) who receive chronic treatment with nonsteroideal antiinflammatory drugs (NSAIDs) or advanced therapies in a clinical setting. It is a cross-sectional study on axSpA patients consecutively recruited from the outpatient clinic of a tertiary hospital. We collected data on clinical and demographic characteristics, as well as treatment patterns involving NSAIDs and advanced therapies. Structural damage was assessed using mSASSS. Overall, data from 193 axSpA patients (83% ankylosing spondylitis) were gathered, with a mean disease duration of 21.4 years. Of these, 85 patients (44%) were exclusively taking NSAIDs, while 108 (56%) were receiving advanced therapies, with TNF inhibitors being the predominant choice (93 out of 108, 86.1%). Among patients using NSAIDs, 64.7% followed an on-demand dosing regimen, while only 17.6% used full doses. Disease activity was low, with a mean BASDAI of 3.1 and a mean ASDAS-CRP of 1.8. In comparison to patients under chronic NSAID treatment, those taking advanced therapies were primarily male (69.4% versus 51.8%, p=0.025) and significantly younger (mean age of 49 versus53.9 years, p=0.033). Additionally, patients on advanced therapies exhibited lower ASDAS-CRP (p=0.046), although CRP serum levels and BASDAI scores did not differ between the two groups. In the multivariable analysis, therapy (NSAID versus biological treatment) was not independently associated with ASDAS-CRP, BASDAI or mSASSS. As a conclusion, this is a crosssectional analysis of a real-world cohort of axSpA patients that shows positive clinical and radiological outcomes for both NSAIDs and advanced therapies.